Intrauterine insemination outcome with and without ovulation induction treatment - Hussein, Adeela h H.; Ahmed, Inas T.; Mahmood, Abeer A. (AL-Kindy College Medical Journal, 2015)
Background:: Infertility is a very common condition affecting approximately 13-14% of couples in the reproductive age. In general population; about 85% of couples have achieved conception within a year. Intrauterine insemination is one of the procedure which have a role in the treatment of infertile couple.Objectives:is to confirm that the use of ovulation induction in the course of intrauterine insemination elevates the pregnancy success rate.Method:This study had been conducted between December 2013 till December 2014 in AL-Elwiyah maternity hospital and AL-Samaraii hospital / Baghdad.On history and clinical examination; the chosen couple had the following criteria; primary infertility for more than one year, no previous IUI trials, husbands with normal seminal fluid analysis, wives in reproductive age group; with regular cycles of 24 – 35 days, body mass index (18-26)kg/m2, normal body contour, no galactorrhea nor hirsutism, normal uterine cavity and patent fallopian tubes by hysterosalpingography. Total number of cases is 76; had been divided into two groups who underwent IUI schedule, 38 cases preceded by ovulation induction and the other 38 cases had spontaneous ovulation by showing a single dominant Graffian follicle size of 18 mm measured by daily vaginal ultrasound.Results:During the study period; the total number of married women participated in the study were 76; divided into two groups. The first group contains 38 women who had the inclusion criteria of our research, underwent IUI after follow up and confirmed spontaneous ovulation, the second group included 38 women who also had the same inclusion criteria and underwent IUI after effective ovulation induction. 5 cases became pregnant while 33 cases didn’t conceive, while in the second group with ovulation induction; 12 cases became pregnant while the remaining 26 cases failed to conceive;Theoverall pregnancy rate was highest(31%) in the group treated with ovulation induction and intrauterine insemination in comparison with the other group which revealed a pregnancy rat.e of only (13%).Conclusion:For fertile couple in which no recognized cause for her infertility ;as for history;clinical examination and investigation are concerned, then combination of ovulation induction with intrauterine inseminationis an effective means for achieivingpregnancyrate by 31%compared with only 13%pregnancy rate in naturally ovulation cycle.